L'egitto dei flavi : sintesi e prospettive d'indagine alla luce della documentazione papirologica ed epigrafica egiziana - Bellucci, Nikola, (Archaeopress Roman archaeology ;, 2020)
Providing synthesis and new prospects of investigation, this text offers an overall review of the various information obtainable from papyrological and epigraphic sources from the Roman province of Egypt at the moment of transition from the Julio-Claudian dynasty to the new Flavian dynasty.